2018
DOI: 10.1103/physrevd.97.043506
|View full text |Cite
|
Sign up to set email alerts
|

Finding the chiral gravitational wave background of an axion- SU(2) inflationary model using CMB observations and laser interferometers

Abstract: A detection of B-mode polarization of the Cosmic Microwave Background (CMB) anisotropies would confirm the presence of a primordial gravitational wave background (GWB). In the inflation paradigm this would be an unprecedented probe of the energy scale of inflation as it is directly proportional to the power spectrum of the GWB. However, similar tensor perturbations can be produced by the matter fields present during inflation, breaking the simple relationship between energy scale and the tensor-to-scalar ratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 76 publications
1
85
0
Order By: Relevance
“…The prototypical cosine potential first associated with natural inflation [13,14] falls under this category for p = 2. This is also the most studied axion potential in Chromo-Natural inflation [15][16][17] along with its Higgsed [29] and spectator variants [30][31][32][33][34][35]. Finally Type III describes an axion monodromy potential, in which the axion probes multiple periods of the modulated potential during inflation.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The prototypical cosine potential first associated with natural inflation [13,14] falls under this category for p = 2. This is also the most studied axion potential in Chromo-Natural inflation [15][16][17] along with its Higgsed [29] and spectator variants [30][31][32][33][34][35]. Finally Type III describes an axion monodromy potential, in which the axion probes multiple periods of the modulated potential during inflation.…”
Section: Modelmentioning
confidence: 99%
“…Ref. [33] addressed this issue for p = 2 and m * = 4, and found that the agreement between numerical and analytic results is excellent for ∆N = 10, while the relative error becomes more than a few percent for ∆N = 5. We expect the slow-roll approximation to break down for ∆N 1, signaling a very sharply peaked gaussian power spectrum.…”
Section: Generalized Cosine Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensor non-Gaussianity can also be an important observable for characterizing the primordial stochastic gravitational wave background at CMB scales, and have been explored in other contexts, see e.g [20,23,107]…”
mentioning
confidence: 99%
“…The information of interest to the present discussion is that the coupling in such theories is typically implemented through a Chern-Simons (CS) term. As a result of the CS coupling, the GW spectrum can be blue or exhibit bump-like features that peak at small scales [45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%